Experience Quality and Destination Loyalty in Malaysian Day Spas: Examining the Direct Role of the PMSE Model - Idrus, Syukurriah; Yusof, Aini Qamariah Mohd; Jamri, Mohamad Hafifi; Hassan, Mohd Sufiean; Abas, Norazira Mohd; Hanapiyah, Zulkefli Muhammad; Ibrahim, Noor Afzaliza Nazira (International Review of Management and Marketing, 2026)
This study investigates how experience quality at wellness day spas in Malaysia, conceptualised through physical, mental, spiritual, and environmental (PMSE) dimensions, influences destination loyalty. Grounded in the Experience Economy framework and recent PMSE developments, it tests a direct-effects model to identify which experiential factors most strongly drive repeat visits and recommendations. Data were collected from 320 spa-goers using a cross-sectional survey and analysed with PLS-SEM (SmartPLS 4). Measurement quality was satisfactory (loadings ≥ .70; CR = .84–.94; AVE = .57–.73; HTMT < .85). Model fit and predictive accuracy were acceptable (SRMR = .061; R² = .61; Q² = .37). Results show that Physical (β = .28, p < .001) and Mental (β = .21, p = .004) experiences significantly and positively influence loyalty, while Spiritual experience also contributes (β = .16, p = .022). Environmental effects were positive but not statistically significant (β = .10, p = .078). The findings highlight the importance of tangible service quality, treatment excellence, and cognitive-affective restoration in enhancing loyalty, with spiritual uplift offering additional benefits. The study contributes to experience-quality theory and provides practical insights for spa operators and policymakers. Future research should explore longitudinal designs and mediated relationships involving satisfaction and trust.